Study on the antioxidant activity of Yangmei juice - CHEN Jian-chu; XIA Qi-le; PAN Xiang-rong; XU Fei-yan (浙江大学学报. 农业与生命科学版)
Juices of four cultivars of Yangmei (Myrica. rubra Sieb. et Zucc), namely Fenhong, Fenghuan, Chida and Liqi, from Yuyao city Zhejiang province were chosen as raw material in this article to investigate the primary physicochemical index, and the antioxidant activity of this fruit. From the results we could draw the conclusion: the ability of scavenging·OH and·O2- radicals was lowest in cultivar Fenhong, which had the lowest anthocyanin, flavonoid and total phenol content, and was superior in cultivar Chida, which had the highest total phenol content. The total phenol content in Yangmei was correlated with its antioxidant ability.